2017
DOI: 10.1002/nau.23244
|View full text |Cite
|
Sign up to set email alerts
|

Structured behavioral treatment research protocol for women with mixed urinary incontinence and overactive bladder symptoms

Abstract: This paper details a perioperative behavioral/pelvic floor exercise intervention research study protocol developed for women undergoing surgery for MUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
0
26
0
3
Order By: Relevance
“…However, teaching people to resist bowel urgency sensations and postpone evacuation has not yet been subject to rigorous research 5 • Bowel urgency may induce feelings of anxiety or panic, which affects ability to concentrate 32 reinforces the person's ability to hold off and the success of urge suppression in a safe environment. • A study of internal anal sphincter pressure wave patterns in 72 adults showed relaxation breathing promotes more regular pressure wave patterns and may aid in reducing fecal urgency and incontinence 54 • Learning to 'stop & squeeze' 41 and experiencing success positively reinforces the chosen urge suppression technique and may lead to improved control of faecal urgency/incontinence • Explanations for bladder training effects include diverting attention away from the urgency sensation using competing mentally demanding activities. 21 This proposed mechanism may be equally applicable to bowel training ➤ The healthcare practitioner positively reinforces the person's continence skills and improved and/or prolonged bowel control.…”
Section: Discussionmentioning
confidence: 99%
“…However, teaching people to resist bowel urgency sensations and postpone evacuation has not yet been subject to rigorous research 5 • Bowel urgency may induce feelings of anxiety or panic, which affects ability to concentrate 32 reinforces the person's ability to hold off and the success of urge suppression in a safe environment. • A study of internal anal sphincter pressure wave patterns in 72 adults showed relaxation breathing promotes more regular pressure wave patterns and may aid in reducing fecal urgency and incontinence 54 • Learning to 'stop & squeeze' 41 and experiencing success positively reinforces the chosen urge suppression technique and may lead to improved control of faecal urgency/incontinence • Explanations for bladder training effects include diverting attention away from the urgency sensation using competing mentally demanding activities. 21 This proposed mechanism may be equally applicable to bowel training ➤ The healthcare practitioner positively reinforces the person's continence skills and improved and/or prolonged bowel control.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized controlled trial (RCT) of 307 older adults, FlexToBa was found to be “enjoyable,” safe and efficacious for improving balance and function . A DVD on bladder training with urge suppression and behavioral measures was developed by a nurse practitioner with extensive experience in behavioral management of UI . Finally, the intervention included a home visit during which a trained study coordinator provided written recommendations for home improvement using a checklist for falls prevention in older adults developed by the Center for Disease Control and Prevention (CDC)…”
Section: Methodsmentioning
confidence: 99%
“…Visual observation can be used to assess a correct pelvic floor muscle contraction, which is seen by perineal elevation, or an incorrect contraction observed by perineal descent in women (Bo et al, 2017). Digital palpation, such as the Brink score and the Laycock power, endurance, repetitions, fast, every, contraction, timed (PERFECT) assessment scheme is the most used method in clinical practice (Laycock and Jerwood, 2001;Newman and Wein, 2013;Newman et al, 2018). The Brink score employs a 4-point scale to assess the contraction pressure, vertical displacement, and endurance of squeeze (Brink et al, 1989).…”
Section: Evaluations Of Pelvic Floor Musclesmentioning
confidence: 99%